2019
DOI: 10.1186/s12916-019-1386-6
|View full text |Cite
|
Sign up to set email alerts
|

The haematological consequences of Plasmodium vivax malaria after chloroquine treatment with and without primaquine: a WorldWide Antimalarial Resistance Network systematic review and individual patient data meta-analysis

Abstract: Background Malaria causes a reduction in haemoglobin that is compounded by primaquine, particularly in patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency. The aim of this study was to determine the relative contributions to red cell loss of malaria and primaquine in patients with uncomplicated Plasmodium vivax . Methods A systematic review identified P. vivax efficacy studies of chloroquine with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 52 publications
3
37
1
Order By: Relevance
“…The presence of confounding factors like COVID-19 infection, suspected DIC with high D-dimer, concurrent administration of lopinavir, along with lack of robust supporting evidence preclude establishing hydroxychloroquine as the sole cause for hemolysis in the patient. To conclude, linking CQ-HCQ with hemolysis in G6PD-deficient subjects based on the present report with above-mentioned confounding factors and inconsistencies is against the established scientific evidence [3][4][5].…”
contrasting
confidence: 55%
See 2 more Smart Citations
“…The presence of confounding factors like COVID-19 infection, suspected DIC with high D-dimer, concurrent administration of lopinavir, along with lack of robust supporting evidence preclude establishing hydroxychloroquine as the sole cause for hemolysis in the patient. To conclude, linking CQ-HCQ with hemolysis in G6PD-deficient subjects based on the present report with above-mentioned confounding factors and inconsistencies is against the established scientific evidence [3][4][5].…”
contrasting
confidence: 55%
“…A seminal study by Youngster et al [3] refuted such claims and categorically suggested the lack of evidence of CQ (thus its hydroxy derivative, HCQ) causing hemolysis in patients with G6PD-deficiency. A recent meta-analysis of clinical trials in CQ+/-primaquine, did not demonstrate a significant drop in hemoglobin from baseline in G6PDdeficients on CQ monotherapy [5]. No incidents of hemolysis were observed in 11 G6PD-deficient patients even after >700 months of HCQ exposure as per the largest US study that examined the occurrence of hemolysis with hydroxychloroquine [4].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Relapse is the main source of P. vivax infection in areas of low endemicity and contributes to chronic anaemia. A recent metanalysis confirms that, despite short term risk of haemolysis, radical cure with primaquine improves hematologic outcomes in the long term [33]. In most P. vivax-endemic regions, anaemia is a major public health problem, which contributes to maternal mortality [34].…”
Section: Resultsmentioning
confidence: 99%
“…The peripheral blood smear anomalies that are orientated with a G6PD deficiency diagnosis, such as hemi-ghost cells, were increasing from day-4 until day-7 (one day after administration of single large dose of hydroxychloroquine). Based on these factors, one can safely ascertain that hemolysis (and hemolytic parameters) gradually increased from day-1 to reach the peak around 4 As the authors have rightly mentioned, there are no guidelines that recommend baseline G6PD evaluation for hydroxychloroquine prescriptions. 5 The presumed caution on using hydroxychloroquine in G6PD deficients is not supported by clinical evidence, but by drug information resources and drug package inserts.…”
Section: Doubtful Precipitation Of Hemolysis By Hydroxychloroquine Inmentioning
confidence: 99%